A temperate Siphoviridae bacteriophage isolate from Siberian tiger enhances the virulence of methicillin-resistant Staphylococcus aureus through distinct mechanisms. Issue 1 (31st December 2022) - Yang, Dan; Wang, Shuang; Sun, Erchao; Chen, Yibao; Hua, Lin; Wang, Xiangru; Zhou, Rui; Chen, Huanchun; Peng, Zhong; Wu, Bin
ABSTRACT: The emergence and worldwide spread of Methicillin-resistant Staphylococcus aureus (MRSA) pose a threat to human health. While bacteriophages are recognized as an effective alternative to treat infections caused by drug resistant pathogens, some bacteriophages in particular the temperate bacteriophage may also influence the virulence of the host bacteria in distinct ways. In this study, we isolated a bacteriophage vB_Saus_PHB21 from an epidermal sample of Siberian tiger ( Panthera tigris altaica ) using an MRSA strain SA14 as the indicator. Our following laboratory tests and whole genome sequencing analyses revealed that vB_Saus_PHB21 was a temperate bacteriophage belonging to the Siphoviridae family, and this bacteriophage did not contain any virulence genes. However, the integration of PHB21 genome into the host MRSA increased the bacterial capacities of cell adhesion, anti-phagocytosis, and biofilm formation. Challenge of the lysogenic strain (SA14 + ) caused severe mortalities in both Galleria mellonella and mouse models. Mice challenged with SA14 + showed more serious organ lesions and produced higher inflammatory cytokines (IL-8, IFN-γ and TNF-α) compared to those challenged with SA14. In mechanism, we found the integration of PHB21 genome caused the upregulated expression of many genes encoding products involved in bacterial biofilm formation, adherence to host cells, anti-phagocytosis, and virulence. This study may provide novel knowledge of "bacteria-phage-interactions" in MRSA.